2021
DOI: 10.1016/j.agwat.2020.106583
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustainable soil and water protection: The perspective of agricultural water price regulation on environmental protection

Abstract: With the development of Chinese economy, more and more attention has been paid to environmental protection, the implementation of water price policy affects economic and environmental changes in China. This paper analyzes the impact of water price policy on agricultural land use and the scale of water pollution discharge in 240 cities in China between 2001 and 2017, by including data from China Urban Statistical Yearbook and China Land & Resources Almanac. The theoretical analysis of this study indicates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…If the price of water does not reflect its true cost, this will affect the most valuable uses of water resources even in water-rich and developed regions. Some literature (Rogers et al, 2002;Iglesias & Blanco, 2008;Amayreh et al, 2011;Chou et al, 2020) show that increased water prices improve managerial efficiencies in the agricultural sector, reduce water consumption, provide economic incentives to reduce water losses and facilitate re-allocation from irrigation to domestic and industrial, increase funding for irrigation support and improve the O&M efficiency of irrigation systems, promote water-saving technologies, and so on. These advantages of water prices are also evident in water-rich and developed regions.…”
Section: Does Water Pricing Should Apply In Water-rich and Developed Regions?mentioning
confidence: 99%
See 1 more Smart Citation
“…If the price of water does not reflect its true cost, this will affect the most valuable uses of water resources even in water-rich and developed regions. Some literature (Rogers et al, 2002;Iglesias & Blanco, 2008;Amayreh et al, 2011;Chou et al, 2020) show that increased water prices improve managerial efficiencies in the agricultural sector, reduce water consumption, provide economic incentives to reduce water losses and facilitate re-allocation from irrigation to domestic and industrial, increase funding for irrigation support and improve the O&M efficiency of irrigation systems, promote water-saving technologies, and so on. These advantages of water prices are also evident in water-rich and developed regions.…”
Section: Does Water Pricing Should Apply In Water-rich and Developed Regions?mentioning
confidence: 99%
“…Zhu et al (2018) used a Bayesian network to analyze the current water rights trading and management systems in Xinjiang with the participation of stakeholders and experts. Chou et al (2020) analyzed the impact of water price policy on agricultural land use in China. The above studies showed the great significance of water prices in solving the problem of water shortage.…”
Section: Introductionmentioning
confidence: 99%
“…ETo can be used as basis to compute the evapotranspiration of different crops. To accomplish this, a crop coefficient (Kc) and a water stress coefficient (Ks) are used to convert ETo to the evapotranspiration of a particular crop, considering its development phase and the soil water availability [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation scheduling can be performed using different approaches, but it is commonly based on reference evapotranspiration (ETo), which is typically computed using meteorological data [2][3][4][5][6][7]. ETo can be used as basis to compute the evapotranspiration of different crops.…”
Section: Introductionmentioning
confidence: 99%
“…With an increasing amount of water transferred from agriculture to ecology, the conservation function of water resources plays a positive role in arid areas, for example in controlling soil desertification, restoring dry downstream lakes, and improving local climatic conditions. At the same time, from the perspective of greenhouse gas emissions, natural desert ecosystems produce lower CH 4 and N 2 O emissions than farmland ecosystems [3,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%